Adesão ao tratamento farmacológico em doentes renais crônicos atendidos pelo ambulatório do Hospital Universitário Walter Cantídio - Moreira, Leonardo Barbosa (2005)
Chronic kidney disease (CKD) is currently an important public health problem. At more advanced stages CKD can take to end-stage renal disease, that request dialysis or renal transplantation. Retard of the progression of CKD depends on the effectiveness of underlying conditions pharmacotherapy. Medication non-compliance harms reaching therapeutic goals. Non-compliance associated factors study is important so that well happened intervention strategies can be implemented. The objective of the present study is to measure the prevalence of medication noncompliance and to identify medication non-compliance related factors in CKD patients. A cross-sectional study was performed at renal outpatient care unit of the Academical Hospital Walter Cantídio, in Fortaleza (CE), between 2004 november and 2005 april. The sample was constituted by 130 CKD patients, at least 18 years old, continuously taking some self-administered antihypertensive or immunosuppressive drug and not being submitted to dialysis or renal transplantation. Non-compliance was measured by questionnaire, physician assessment and outcomes methods, being considered non-compliant patients if non-compliance has been detected by any method. Independent variables studied were related to sociodemographic characteristics, characteristics and patients’ perceptions on CKD, its treatment and offered service and information level about pharmacotherapy. Database and bivariate analysis were performed at EPI-INFO version 6.04d, using Yates corrected chi-square and isher’s exact tests. A multivariate analysis was conducted through a logistic regression model using SPSS for Windows version 10.0. Confidence level for all tests was p < 0,05 (two-tailed). Frequency of non-compliant patients, detected by any method, was 61,3% (95%CI = 52,0 – 70,1%). Multivariate analysis results showed that less than 5 years CKD diagnosis time (p = 0,015), selfreport of adverse drug reaction (p = 0,015) and low information level about pharmacotherapy (p = 0,028) presented statistically significant association with noncompliance. As greater the information level about pharmacotherapy smaller the noncompliance prevalence. Medication non-compliance prevalence is high among studied patients. Factors associated with non-compliance are possible causes of this comportment. Educational and motivational interventions are necessary for decrease problem’s magnitude. Observed results are coherent with literature, however, more studies are necessary to evaluate causes of the medication non-compliance on CKD and effectiveness of the proposed interventions.